1996
DOI: 10.1083/jcb.132.6.1105
|View full text |Cite
|
Sign up to set email alerts
|

Binding to cadherins antagonizes the signaling activity of beta-catenin during axis formation in Xenopus.

Abstract: Abstract. 13-Catenin, a cytoplasmic protein known for its association with cadherin cell adhesion molecules, is also part of a signaling cascade involved in embryonic patterning processes such as the determination of the dorsoventral axis in Xenopus and determination of segment polarity in Drosophila. Previous studies suggest that increased cytoplasmic levels of 13-catenin correlate with signaling, raising questions about the need for interaction with cadherins in this process. We have tested the role of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
216
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(238 citation statements)
references
References 44 publications
20
216
2
Order By: Relevance
“…19 In healthy epithelial cells, E-cadherin plays an important role in cell-cell adhesions by homophilic interaction on adjacent cells. 18,19 Our experiments have demonstrated that MT1A2 cells express E-cadherin, maintain cell-cell adhesions, and also express EphA2 and EphrinA1 on the cell surface, but the majority of EphA2 remains unphosphorylated suggesting that Ecadherin alone is not effective in mediating EphrinA1 interaction with EphA2.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…19 In healthy epithelial cells, E-cadherin plays an important role in cell-cell adhesions by homophilic interaction on adjacent cells. 18,19 Our experiments have demonstrated that MT1A2 cells express E-cadherin, maintain cell-cell adhesions, and also express EphA2 and EphrinA1 on the cell surface, but the majority of EphA2 remains unphosphorylated suggesting that Ecadherin alone is not effective in mediating EphrinA1 interaction with EphA2.…”
Section: Discussionmentioning
confidence: 92%
“…18,19 It has been proposed that phosphorylation levels of tyrosine kinases maintain a balance between cell-extracellular matrix and cell-cell adhesions. 20 Apparently, MT1A2 cells seem to have better cell-to-cell adhesions compared to MDA-MB-231 cells (data not shown).…”
Section: Epha2 Expression and Phosphorylation In Had Vector-infected mentioning
confidence: 99%
“…There is also evidence that cadherins can sequester catenins away from the Wnt signal (58,59). Therefore, down-regulation of Ncadherin by Wnt-3A may serve a dual function in our system, i.e.…”
Section: Wnt-3a Signaling In Bmp-2-mediated Chondrogenesismentioning
confidence: 99%
“…Binding of-catenin to E-cadherin protects Ecadherin from degradation [79]. Additionally, the interaction between these two proteins helps regulate -catenin signaling in the cell: one study found that overexpressing cadherins resulted in sequestration of the cytosolic pool of -catenin leading to reduced -catenin signaling [134]. Another study found that E-cadherin competed with LEF-1, one of -catenin's transcriptional factor binding partners, for binding to -catenin.…”
Section: Modulation Of β-Catenin At the Cell Membranementioning
confidence: 99%
“…However, the protein has been found to bind to the nuclear envelope directly. Additionally, translocation of -catenin is energy-dependent, suggesting that it can be imported into the nucleus independent of a signal sequence or other proteins [134].…”
Section: β-Catenin Nuclear Translocation and Transcriptional Activitymentioning
confidence: 99%